Adsorption and catalytic oxidation of asphaltenes in fumed silica nanoparticles: Effect of the surface acidity (2016)
This study aims to evaluate the effect of surface acidity of fumed silica nanoparticles in adsorption and subsequent thermal cracking of Colombian asphaltenes. The acidities of the surfaces were established through Temperature Programed Desorption (TPD) experiments. The adsorption equilibrium of asphaltenes was determined using a static batch method, and the data obtained was fitted using the Langmuir model, the Freundlich model and the SLE Model. Asphaltenes catalytic oxidation experiments were conducted, and it was found that this process was surface nature dependent. In all cases, the temperature of asphaltenes oxidation was reduced regarding the virgin asphaltene sample. The effective activation energies were estimated with the iso-conversional OFW method. This energy was found to be related to adsorption affinity and asphaltenes self-association on nanoparticles surface.